Conservation implications of divergent global patterns of ant and vertebrate diversity. Issue 8 (3rd May 2013) - Jenkins, Clinton N.; Guénard, Benoit; Diamond, Sarah E.; Weiser, Michael D.; Dunn, Robert R.; Roura‐Pascual, Núria
Abstract Aim Global conservation planning is often oriented around vertebrates and plants, yet most organisms are invertebrates. To explore the potential conservation implications of this bias, we assessed how well patterns of diversity for an influential group of invertebrates, the ants, correspond with those of three vertebrate groups (birds, mammals and amphibians). Location Global. Methods We compiled data on the number of genera of ants and the three vertebrate groups for 370 political regions across the world. We then compared their correlations both for overall diversity and between subsets of genera likely to be of conservation concern. We also developed generalized additive models (GAM) to identify regions where vertebrates and ants diverged in their diversity patterns. Results While ant and vertebrate diversity do positively correlate, the correlations are substantially weaker for the ant lineages of the greatest conservation concern. Vertebrates also notably fail to predict ant diversity in specific geographic areas, including Australia and Southeast Asia, parts of Africa and Madagascar, and south‐western China. These failures may be genuine differences in diversity patterns, or they may indicate important gaps in our knowledge of ant and vertebrate diversity. Main conclusions We conclude that it is currently unwise to assume that global conservation priorities based on vertebrates will conserve ants as well. We suspect that this also applies to other invertebrates.